Pengaruh Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa di Kelas V UPTD SDN 124394 Pematang Siantar - Asima Rohana Panjaitan; Nancy Angelia Purba; Partohap S.R. Sihombing (Journal on Education, 2023)
This study aims to determine the effect of parenting style on the learning motivation of fifth grade students at SD Negeri 124394 Pematang Siantar in the 2022/2023 academic year. In this study, researchers used a type of quantitative research. The population in this study were all fifth grade students, totaling 50 people using the entire population as the research sample. The process of collecting data using observation instruments, questionnaires and documentation, by using data analysis techniques instrument test, prerequisite test, descriptive statistics and hypothesis testing. The results of this study indicate that the value of tcount ˃ ttable is 3.627 ˃ 1.056 and with a significance value of 0.002 ˂ 0.05 and produces an R Square of 0.409, so it is concluded that social interaction has an effect of 40.9% on thematic learning outcomes of class IV students at SDN 124386 Pematang Siantar.